Long-hairy Xyalidae (Nematoda, Chromadoria, Monhysterida) in the White Sea; New Species, New Combinations, and the Status of the Genus Trichotheristus) (Volosatye Xyalidae (Nematoda, Chromadoria, Monhysterida) v Belom More: Novye Vidy, Novye Kombinatsii i Status Roda Trichotheristus) - Tchesunov, A. V. (Zoologicheskii Zhurnal, 1990)
Locality: ; Cabinet:
NeMys doc_id: 6455 NeMys doc_id: 4211